2019
DOI: 10.3390/foods8100484
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Terminology for Snack Foods and Their Texture by Consumers in Four Languages: A Qualitative Study

Abstract: The choice of food products is affected by the combination of food properties, consumer motives, emotions, and context, especially in cross-cultural studies. The designs of cross-cultural studies involve several limitations such as conceptual perception and linguistic and cultural differences in response style. These factors confine the validity and generalizability of such study models. In this study, we have combined linguistic and contextual perception together to generate consumer texture terminologies. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…This finding may reflect the close relationship between language and culture [ 24 ]. Past work has found that linguistic and cultural differences are important factors that affect the way people respond in multi-country interventions [ 25 ]. For example, a major driver for food choices in western countries is taste.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may reflect the close relationship between language and culture [ 24 ]. Past work has found that linguistic and cultural differences are important factors that affect the way people respond in multi-country interventions [ 25 ]. For example, a major driver for food choices in western countries is taste.…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of these texture attributes are measurable and manipulatable to predict and develop new product candidates. Since texture has been identified as an important function of snack foods from which derive consumer desired benefits [ 64 , 100 ], and serves as the base of many snack food development projects, knowing those existing attributes is key information, both to provide reference points for “me-too” products and for companies interested in finding new opportunities. The descriptive analysis helped to quantify product attributes and translate them into measurable product characteristics [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The focus group procedure provides a way to obtain qualitative data on various aspects of consumer choice (Chambers IV & Smith, 1991). In addition, it is a commonly used technique that allows researchers to probe and gain insight into the motivations for choice behavior and word meanings (Kumar & Chambers IV, 2019; Pires, de Noronha, & Trindade, 2019; Talavera & Sasse, 2019). Flexibility in understanding different concepts through discussion can facilitate the depth and breadth of the output.…”
Section: Methodsmentioning
confidence: 99%